MARS/NDRI/KSU Communications Workshop: Part 7B. Safe food for a healthier Nepal: Priming a national mycotoxin response - Harvey, Jagger J.W. (My University, 2022)
• Low aflatoxin awareness/risky agricultural practices • Poor drying and storage practices, need for innovation packages at multiple value chain entry points (on farm, including as service provision or community-based efforts; traders/aggregators; market vendors,..) • Research capacity has been enhanced; however, expanded, hub-spoke, surveillance/mitigation, risk communication capacity is needed (provinces, academia,…) • Pair enabling policy with private sector
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication